Control of bacterial wilt (Ralstonia solanacearum) in potato (Solanum tuberosum) using rhizobacteria and arbuscular mycorrhiza fungi. - Aguk, J.A.; Karanja, N.; Schulte-Geldermann, Elmar; Bruns, C.; Kinyua, Z.; Parker, M. (African Journal of Food, Agriculture, Nutrition and Development, 2018)
Bacterial wilt disease, race 3 biovar 2A, is a devastating disease of potato and other important solanaceous crops, with no chemical control method. The current studies were, therefore, undertaken to assess the efficacy of biocontrol agent (BCA) and organic amendments to manage bacterial wilt (BW) of potato caused by Ralstonia solanacearum, under controlled conditions. The present studies evaluated disease severity, latent infection, arbuscular mycorrhiza fungi (AMF) root colonization and tuber number and weight on two potato cultivars upon inoculation with AMF, rhizobacteria in various combinations and organic amendments which included poultry manure, cow manure and compost. Disease severity was more pronounced in CIP 381381.13 (Tigoni) than in CIP 387164.4 (Clone). Glomus intradices + Bacillus spp. and G. etunicatum + Bacillus spp. for both cultivars and for the Clone, G. intradices + Pseudomonas spp., Pseudomonas spp. + Bacillus spp. + Azoctobacter spp. had area under disease progress curve (AUDPC) of zero. These were also the treatments with the highest AMF root colonization ranging from 50-36 compared to the controls with zero AMF root colonization and also tested negative for latent infection test except for G. etunicatum + Bacillus spp. in Tigoni. Poultry manure had AUDPC of 33 and 42 in Tigoni and clone, respectively compared with cow manure with 56 and 43 and compost with 54 and 42 in Tigoni and clone. A repeat of the trial involving the promising treatments, however, had all treatments having BW infected tubers. There was no significant difference (P≤0.05) in tuber number and weight in the BCA treatments with half fertilizer application and complete fertilized control. Mycorrhizal root colonization ranged from 23-49% in AMF inoculated treatments while no colonization was observed in the controls. The BCAs were effective as biocontrols against bacterial wilt even in the susceptible cultivar. More studies especially under field conditions are needed to further determine the response of the BCAs and organic amendments under different soil conditions.